2004
DOI: 10.1258/002221504323086589
|View full text |Cite
|
Sign up to set email alerts
|

Swallowed nasal pack: a rare but serious complication of the management of epistaxis

Abstract: Packing of the nose with a suitable material remains a popular method of treating epistaxis. The authors report a serious complication of a new design of nasal pack; Rapid Rhino, which was swallowed during the treatment of a patient with epistaxis, resulting in bowel perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…In addition, insertion of an endotracheal tube may result in dislodgment of foreign bodies deeper into the airway, with very serious consequences, including total airway obstruction and death. As reported by Hashmi and colleagues [3], nasal packing material infrequently migrates into the supraglottic area and causes airway obstruction. What is more interesting is that this may occur regardless of the operator's skills (surgeon vs paramedic [1,2]).…”
Section: Replymentioning
confidence: 77%
“…In addition, insertion of an endotracheal tube may result in dislodgment of foreign bodies deeper into the airway, with very serious consequences, including total airway obstruction and death. As reported by Hashmi and colleagues [3], nasal packing material infrequently migrates into the supraglottic area and causes airway obstruction. What is more interesting is that this may occur regardless of the operator's skills (surgeon vs paramedic [1,2]).…”
Section: Replymentioning
confidence: 77%
“…In addition, it is recommended to secure the string of Merocel to the nasal dorsum or cheek. However, Hashmi et al [24] reported a case of a nasal pack being swallowed during the treatment of epistaxis, which caused bowel obstruction and perforation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this may be exacerbated by aspiration of blood or by the use of sedative agents during insertion of the packs 1 . Swallowed nasal pack has also been reported as a rare but serious complication, resulting in perforation and peritonitis, requiring laparotomy 13 …”
Section: Discussionmentioning
confidence: 99%
“…Epistaxis occurs as a result of interaction of factors: damage to the nasal mucosal lining, disruption of vessel wall integrity, or alteration to the haemostatic system 1 . These include environmental (humidity, temperature), medications (nasal sprays, anticoagulant, anti‐platelet, non‐steroidal anti‐inflammatory medications), local (trauma, tumours, vascular and structural lesions) and systemic factors (vessel wall fibrosis in tunica media associated with ageing, hypertension, alcohol abuse, organ failure, coagulopathy) 1–3,6,8–13 . However, it is often (80–90%) that no precipitating cause can be identified 1,3 …”
Section: Introductionmentioning
confidence: 99%